2016
DOI: 10.1016/j.actbio.2016.08.041
|View full text |Cite
|
Sign up to set email alerts
|

A correlative spatiotemporal microscale study of calcium phosphate formation and transformation within an alginate hydrogel matrix

Abstract: The precipitation and transformations of calcium phosphates (CaP) is a complex process, where both formation kinetics and the stability of different mineral phases control the outcome. This situation is even more complex if CaP is precipitated in a hydrogel matrix, where one can expect the organic matrix to modulate crystallization by introducing supersaturation gradients or changing the nucleation and growth kinetics of crystals. In this study we apply a range of characterization techniques to study the miner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…Bact– consist predominantly of OCP and WL inclusions. OCP is identified by a split ν 1 PO 4 3− band and the presence of acid phosphate (HPO 4 2− ) groups (Bannerman et al, 2016; Bjørnøy et al, 2016; Shi et al, 2016). WL exhibits a shift of the ν 1 PO 4 3− band to higher wavenumbers, from ~960 cm −1 (for CHAp) to 968–970 cm −1 , and a shift of the ν 2 PO 4 3− band to lower wavenumbers, from ~430 cm −1 (for CHAp) to 407 cm −1 (de Aza et al, 1997; Wopenka & Pasteris, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Bact– consist predominantly of OCP and WL inclusions. OCP is identified by a split ν 1 PO 4 3− band and the presence of acid phosphate (HPO 4 2− ) groups (Bannerman et al, 2016; Bjørnøy et al, 2016; Shi et al, 2016). WL exhibits a shift of the ν 1 PO 4 3− band to higher wavenumbers, from ~960 cm −1 (for CHAp) to 968–970 cm −1 , and a shift of the ν 2 PO 4 3− band to lower wavenumbers, from ~430 cm −1 (for CHAp) to 407 cm −1 (de Aza et al, 1997; Wopenka & Pasteris, 2005).…”
Section: Resultsmentioning
confidence: 99%
“… 17 The layered spherical materials with a hierarchical structure, which are designed to fill the volumes of the complex shapes during the restoration of bone tissue, have been used as biomedical materials. 18 , 19 To improve the functional properties of the implant material, the compositions of calcium phosphate, silicon, and titanium are crucial. 20 − 24 It has been reported that the presence of silicon on the surface of the phosphate–calcium material accelerates the bonding of the implant with the bone (osseointegration).…”
Section: Introductionmentioning
confidence: 99%
“…The process of bone tissue remodeling occurs about twice faster on silicon-containing hydroxyapatite (SiHA) than on hydroxyapatite in the absence of silicon (Petrovskaya et al 2016; Bjornoy et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Silicate groups in the calcium–phosphate system significantly increase the rate of osteogenesis in vivo after implantation. The process of bone tissue remodeling occurs about twice faster on silicon-containing hydroxyapatite (SiHA) than on hydroxyapatite in the absence of silicon (Petrovskaya et al 2016; Bjornoy et al 2016).…”
Section: Introductionmentioning
confidence: 99%